การศึกษาประสิทธิภาพชุดฝึกอบรมการบูรณาการพหุปัญญาในการจัดการเรียนการสอนภาษาอังกฤษ (A STUDY OF THE EFFECTIVENESS OF THE TRAINING KIT ON AN INTEGRATION OF MULTIPLE INTELLIGENCES IN ENGLISH LANGUAGE CLASSROOMS) - ศรีคุรุวาฬ รัชนีย์; พิบูลชล เฉลียวศรี; วงษ์อยู่น้อย สมสรร (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2011)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาประสิทธิภาพของชุดฝึกอบรมในการพัฒนาความรู้และความเข้าใจเรื่องพหุปัญญา และในการเสริมสร้างสมรรถภาพการนำความรู้เรื่องพหุปัญญาไปประยุกต์ในการจัดการเรียนรู้ กลุ่มตัวอย่างประกอบด้วยครูผู้สอนภาษาอังกฤษที่มีประสบการณ์การสอนภาษาอังกฤษในระดับชั้นต่างๆ จำนวน 12 ท่าน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แผนการฝึกอบรมซึ่งแบ่งเป็นภาคทฤษฎี และภาคปฏิบัติจำนวนเจ็ดแผน แบบทดสอบวัดความรู้และความเข้าใจเรื่องพหุปัญญาของครูผู้เข้ารับการอบรมก่อนและหลังการฝึกอบรม แบบประเมินแผนการสอน และแบบสังเกตการสอนใช้ประเมินความสามารถของครูผู้เข้ารับการอบรมในการนำความรู้เรื่องพหุปัญญาไปใช้ในการจัดการเรียนรู้ ผู้วิจัยใช้สถิติทดสอบของแมนวิทนีย์ในการเปรียบเทียบคะแนนจากแบบทดสอบก่อนและหลังการฝึกอบรม จากผลการวิจัยพบว่า ความรู้และความเข้าใจเรื่องพหุปัญญาของครูผู้เข้ารับการอบรมก่อนและหลังการฝึกอบรมไม่แตกต่างกันอย่างมีนัยสำคัญ และพบว่าชุดฝึกอบรมสามารถเสริมสร้างและพัฒนาความสามารถในการนำความรู้เรื่องพหุปัญญาไปประยุกต์ในการสร้างแผนการเรียนรู้และการจัดการเรียนรู้การสอนของครูผู้เข้ารับการอบรมในระดับปานกลาง คำสำคัญ: พหุปัญญา ชุดฝึกอบรม การจัดการเรียนการสอนภาษาอังกฤษ This study aimed to measure how effectively the training kit enhanced the teacher trainees’ knowledge of the concept of multiple intelligences (MI). It also aimed at measuring how effectively the kit could enable the teacher trainees to construct lesson plans integrated with the concept of MI and apply them in their teaching practice. The teacher trainees who participated in this study involved 12 experienced English language teachers who taught English as a foreign language to various grade level students under the basic education core curriculum of Thailand. The research instruments consisted of seven training plans, the test on the concept of multiple intelligences which was used as a pre-test and post-test to measure the development of the teacher trainees’ knowledge and the observation tools which were employed to collect data on the teacher trainees’ ability to construct and apply lesson plans integrated with the concept of MI. Mann Whitney U-test statistic was employed to compare the results from the pre-test and post-test. The results revealed that the teacher trainees’ knowledge of the concept of MI before the training was insignificantly different from their knowledge after the training. The training kit could moderately provide necessary skills for the teacher trainees to construct lesson plans integrated with the concept of MI and the teacher trainees could fairly apply lesson plans integrated with the concept of MI in their teaching practice. Keywords: Multiple intelligences, Training kit, English language classroom